2012
DOI: 10.1080/09658211.2012.708345
|View full text |Cite
|
Sign up to set email alerts
|

Children's eyewitness memory: Repeating post-event misinformation reduces the distinctiveness of a witnessed event

Abstract: Children may incorporate misinformation into reports of witnessed events, particularly if the misinformation is repeated. One explanation is that the misinformation trace is strengthened by repetition. Alternatively, repeating misinformation may reduce the discriminability between event and misinformation sources, increasing interference between them. We tested trace strength and distinctiveness accounts by showing 5- and 6-year-olds an event and then presenting either the "same" or "varying" items of post-eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Additionally, few studies have examined developmental changes in children's susceptibility to the misinformation effects specifically during middle childhood. Most past studies examining misinformation effects in children have focused on early childhood (e.g., Bright‐Paul & Jarrold, , ; Elischberger, ; Memon, Holliday, & Hill, ; Roberts & Powell, ; Roebers & Schneider, ) or age‐related differences between early and middle childhood (e.g., Bright‐Paul, Jarrold, & Wright, ; Holliday, Douglas, & Hayes., ; London et al ., ; Pezdek & Roe, ; Poole & Lindsay, ). Yet child witnesses who fall in the middle childhood age group are more likely than younger child witnesses to testify in criminal cases (e.g., Goodman et al ., ; Gray, ; Quas & Goodman, ).…”
Section: Misinformation Effects and Compliancementioning
confidence: 99%
“…Additionally, few studies have examined developmental changes in children's susceptibility to the misinformation effects specifically during middle childhood. Most past studies examining misinformation effects in children have focused on early childhood (e.g., Bright‐Paul & Jarrold, , ; Elischberger, ; Memon, Holliday, & Hill, ; Roberts & Powell, ; Roebers & Schneider, ) or age‐related differences between early and middle childhood (e.g., Bright‐Paul, Jarrold, & Wright, ; Holliday, Douglas, & Hayes., ; London et al ., ; Pezdek & Roe, ; Poole & Lindsay, ). Yet child witnesses who fall in the middle childhood age group are more likely than younger child witnesses to testify in criminal cases (e.g., Goodman et al ., ; Gray, ; Quas & Goodman, ).…”
Section: Misinformation Effects and Compliancementioning
confidence: 99%
“…Given the important role that eyewitnesses play in criminal investigations, it is crucial to understand how an eyewitness’ memory may be influenced by receiving the same piece of misinformation multiple times and through more than one source (e.g., from multiple people). Although some reports have shown that repeated exposure to misinformation can exacerbate its influence ( Mitchell and Zaragoza, 1996 ; Walther et al, 2002 ; Ecker et al, 2011 ; Bright-Paul and Jarrold, 2012 ; Schwarz et al, 2016 ; Ecker et al, 2020 ), very little research has independently examined the effects of repetition and source variability on eyewitness suggestibility ( Mitchell and Zaragoza, 1996 ; Foster et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, repeated exposure to misinformation increases the misinformation effect ( Mitchell and Zaragoza, 1996 ; Zaragoza et al, 2007 ; Ecker et al, 2011 ; Bright-Paul and Jarrold, 2012 ; Foster et al, 2012 ). This repetition effect has been observed across different participant populations (see Mitchell and Zaragoza, 1996 ; Bright-Paul and Jarrold, 2012 ) and is thought to occur as a result of increased processing fluency or increased belief in the truthfulness of the misinformation (see Arkes et al, 1991 ; Hassan and Barber, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations